Immune system participates in brain regeneration and restoration of reproduction in the earthworm Dendrobaena veneta. Issue 2 (October 2015) - Molnar, Laszlo; Pollak, Edit; Skopek, Zuzanna; Gutt, Ewa; Kruk, Jerzy; Morgan, A. John; Plytycz, Barbara
Highlights: Restoration of cocoon production is a biomarker of brain regeneration in earthworms. Brains extirpated in Prilocaine anesthetized (PE) or electrostimulated (VE) worms. Coelomocytes were depleted in VE but not PE worms. Brains and reproduction were restored faster in PE than in VE worms. Coleomocytes participate in brain regeneration. Abstract: Earthworm decerebration causes temporary inhibition of reproduction which is mediated by certain brain-derived neurohormones; thus, cocoon production is an apposite supravital marker of neurosecretory center functional recovery during brain regeneration. The core aim of the present study was to investigate aspects of the interactions of nervous and immune systems during brain regeneration in adult Dendrobaena veneta (Annelida; Oligochaeta). Surgical brain extirpation was combined, either with (i) maintenance of immune-competent coelomic cells (coelomocytes) achieved by surgery on prilocaine-anesthetized worms or (ii) prior extrusion of fluid-suspended coelomocytes by electrostimulation. Both brain renewal and cocoon output recovery were significantly faster in earthworms with relatively undisturbed coelomocyte counts compared with individuals where coelomocyte counts had been experimentally depleted. These observations provide empirical evidence that coelomocytes and/or coelomocyte-derived factors (e.g. riboflavin) participate in brain regeneration and, by implication, that there is close functional synergy between earthworm neural and immune systems.